Theoretical and experimental analyses of casing collapsing strength under non-uniform loading - Lin, Yuan-hua; Deng, Kuan-hai; Zeng, De-zhi; Zhu, Hong-jun; Zhu, Da-jiang; Qi, Xing; Huang, Yun (Journal of Central South University, 2014)
Failure data from oilfield showed that casings which were designed according to API standards were deformed and collapsed in salt formations. The main reason for decrease in strength may be caused by non-uniform loading (NUL) that was not considered in traditional casing collapsing strength design or that the designing method should be improved and developed. Obviously, the calculation of casing collapse strength is one of the key factors in casing design. However, the effect of NUL on casing collapse strength was generally neglected in the present computational methods. Therefore, a mechanical model which can calculate casing collapse strength under NUL was established based on the curved beam theory of the elasticity and was solved using displacement method. Simultaneously, three anti-collapse experiments were performed on C110 casing under NUL, and the strain and deformation laws of three casings in the process of collapse were obtained by the electrical method. Yield limit of every casing was obtained by analyzing those data. Experimental results are consistent with the results of calculation of new model. It indicates that the model can be used to calculate yield limit loading of casings under NUL.